Optimizing plant regeneration and genetic transformation of Paulownia elongata. (May 2021) - Bajaj, Richa; Irvin, Lani M.; Vaidya, Brajesh Nanda; Dhekney, Sadanand A.; Joshee, Nirmal
Abstract: The effects of plant tissue culture media with varying levels of growth regulators and carbon sources was tested on four explant types for organogenesis and plant regeneration in Paulownia elongata . Among the various treatments applied, the best response to adventitious shoot proliferation was observed when entire leaf or half leaf with attached petiole explants were cultured on either MS or B5 medium along with 25 μM thidiazuron, 10 μM indole acetic acid and 30 g L −1 maltose as a carbon source. Proliferated shoots were rooted within five days on a modified MS medium containing 5 μM indole butyric acid and plants were successfully acclimated and hardened for greenhouse transfer. A green fluorescent protein (gfp) and neomycin phosphotransferase II (npt II) gene was used to optimize genetic transformation protocols. Agrobacterium tumefaciens mediated transformation of half leaf with petiole explants produced transgenic plants using the media optimized for shoot proliferation and rooting. The insertion and expression of the GFP transgene was detected using PCR and RT-PCR. Highlights: A highly efficient plant regeneration system was developed. Priming of stock plants enhanced shoot induction and number. Agrobacterium tumefaciens -mediated genetic transformation protocols were optimized.